Enhancing Tax Compliance: The Role of Awareness, Regulation Understanding, and Perceived System Effectiveness Among Self-Employed Individuals - Fuadi, Agus; Wulandari, Dian Sulistyorini; Loka, Sedayu Puspapita (LPPM Universitas Pelita Bangsa, 2024)
Indonesia's national revenue is witnessing substantial annual growth, primarily driven by its diverse natural resources that bolster government income. Among these sources, the tax department is the foremost contributor to the state's revenue. Maintaining the nation's stability and progress requires consistent tax payments from all taxpayers to improve compliance levels. This study examines how taxpayer awareness, understanding of tax regulations, and perceptions of the tax system's effectiveness influence the willingness to pay taxes among individual taxpayers engaged in independent work registered at KPP Pratama Cikarang Selatan. Utilizing random sampling and determining the sample size through the Slovin formula, the study collects responses from 94 respondents within the population of independent workers registered at KPP Pratama Cikarang Selatan. A quantitative approach is employed, with primary data gathered through questionnaires and analyzed using multiple linear regression analysis. The results reveal that understanding tax regulations and perceptions of the tax system's effectiveness positively impact the willingness to pay taxes, while taxpayer awareness does not have a significant influence. Furthermore, collectively, taxpayer awareness, comprehension of tax regulations, and perceptions of the tax system's effectiveness significantly affect the willingness to pay taxes among individual taxpayers engaged in independent work registered at KPP Pratama Cikarang Selatan.